Brexit and tourism : process, impacts and non-policy - Hall, Derek R. (Aspects of tourism, 2020)
"This book offers a multidisciplinary, holistic appraisal of the implications of the UK's withdrawal from the European Union (EU) for tourism and related mobilities. It attempts to look beyond the short- to medium-term consequences of these processes for both the UK and the EU"--